IMPLEMENTATION OF GUIDED INQUIRY LEARNING USING PHET SIMULATION ON KINETIC THEORY OF GASES TOPIC FOR INCREASING THE LEARNING OUTCOME OF GRADE XI STUDENTS AT SMAN 13 SURABAYA - FITRI DAMAYANTI, RISKI (Inovasi Pendidikan Fisika, 2017)
This research aimed to analyze the learning feasibility, student learning outcome, and response toward guided inquiry learning using PhET Simulation on kinetic theory of gases topic. Learning outcome are knowledge and skill aspect. The type of this research is pre-experimental with one group pretest-posttest design by using one experiment class and one replication class. Subject of research are students at grade XI IPA 5 and XI IPA 6 in SMAN 13 Surabaya. Instruments of research are learning feasibility observation sheet, pretest posttest sheets and students response sheet. The improvment of learning outcome was analyzed by t-test and gain score. The result shows that (1) learning feasibility was done in excellent  category; (2) improving of knowledge and skill learning outcome in two classes are significant in high category; (3) students show positive response to the treatment applied in very good category. Based on the data, it can concluded that the guided inquiry learning using PhET Simulation on kinetic theory of gases can increase learning outcome of grade XI student at SMAN 13 Surabaya. Key words: guided inquiry, PhET Simulation, theory kinetic of gases